The Effect of Training toward PT Employee Performance. EKK - Fauzobihi, Fauzobihi; Meidianita, Riska; Lesmana, Yanto (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research aims to determine the effect of training on employee performance at PT. EKK in Bekasi city. The method used is a quantitative descriptive method using SPSS techniques. The sample taken in this research was a saturated sampling technique, where the entire population was sampled, namely 110 people. The data collection technique used in this research is the questionnaire method. The data analysis used is validity test, reliability test, simple linear regression, correlation coefficient, coefficient of determination, and hypothesis testing. This research shows the strong influence of training (X) on employee performance (Y) with a regression of Y = 7.352 + 0.815X, the regression coefficient number is 0.815, which means that training has a positive effect of 0.815. The coefficient of determination value is 41.5% while the remaining 58.5% is influenced by other factors. Hypothesis testing obtained t-count > t-table or (8.746 > 1.980), this is reinforced by the probability significance of 0.000 < 0.05. Thus, H0 is rejected and Ha is accepted, meaning that there is a significant influence between training and employee performance at PT. EKK. Companies should always pay attention and provide opportunities for employees to take part in training, so that employee competency can be maintained or improved and will support employee performance.